Determination of copper at wide range concentrations using instrumental features of high-resolution continuum source flame atomic absorption spectrometry - Lima, Renata Toledo; Raposo Júnior, Jorge Luiz; Virgílio, Alex; Gomes Neto, José Anchieta (Eclética Química, 2010)
This work describes a method to determine Cu at wide range concentrations in a single run without need of further dilutions employing high-resolution continuum source flame atomic absorption spectrometry. Different atomic lines for Cu at 324.754 nm, 327.396 nm, 222.570 nm, 249.215 nm and 224.426 nm were evaluated and main figures of merit established. Absorbance measurements at 324.754 nm, 249.215 nm and 224.426 nm allows the determination of Cu in the 0.07 – 5.0 mg L-1, 5.0 – 100 mg L-1 and 100 – 800 mg L-1 concentration intervals respectively with linear correlation coefficients better than 0.998. Limits of detection were 21 μg L-1, 310 μg L-1 and 1400 μg L-1 for 324.754 nm, 249.215 nm and 224.426 nm, respectively and relative standard deviations (n = 12) were £ 2.7%. The proposed method was applied to water samples spiked with Cu and the results were in agreement at a 95% of confidence level (paired t-test) with those obtained by line-source flame atomic absorption spectrometry.